2015
DOI: 10.1002/ece3.1603
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquity of phenotypic plasticity in plants: a synthesis

Abstract: Adaptation to heterogeneous environments can occur via phenotypic plasticity, but how often this occurs is unknown. Reciprocal transplant studies provide a rich dataset to address this issue in plant populations because they allow for a determination of the prevalence of plastic versus canalized responses. From 31 reciprocal transplant studies, we quantified the frequency of five possible evolutionary patterns: (1) canalized response–no differentiation: no plasticity, the mean phenotypes of the populations are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
148
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(156 citation statements)
references
References 64 publications
7
148
1
Order By: Relevance
“…In another similar meta‐analysis (Davidson et al., 2011), the invasive species considered were more phenotypically plastic overall, but such plasticity was not associated with fitness gains. This is consistent with the perspective that local adaptation is a more common mechanism than phenotypic plasticity allowing plants to deal with environmental variability (Palacio‐López et al., 2015). Several studies have reported different sets of local adaptations to different non‐native ranges for several traits of the same Centaurea species studied here (García, Callaway, Diaconu, & Montesinos, 2013; Graebner, Callaway, & Montesinos, 2012; Montesinos et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another similar meta‐analysis (Davidson et al., 2011), the invasive species considered were more phenotypically plastic overall, but such plasticity was not associated with fitness gains. This is consistent with the perspective that local adaptation is a more common mechanism than phenotypic plasticity allowing plants to deal with environmental variability (Palacio‐López et al., 2015). Several studies have reported different sets of local adaptations to different non‐native ranges for several traits of the same Centaurea species studied here (García, Callaway, Diaconu, & Montesinos, 2013; Graebner, Callaway, & Montesinos, 2012; Montesinos et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of 31 reciprocal transplant experiments considering 362 traits showed that 52% of the studied traits were not plastic, and that among the 48% of traits showing some kind of plasticity, 31% of it were nonadaptive. These results suggest that local adaptation might be a more common response to variable environments than adaptive phenotypic plasticity (Palacio‐López, Beckage, Scheiner, & Molofsky, 2015). A second meta‐analysis (Liao et al., 2016) suggested that phenotypic plasticity explained a higher proportion of phenotypic variation in clonal, self‐compatible, and perennial species, whereas local adaptation explained more phenotypic variation for annual species.…”
Section: Introductionmentioning
confidence: 98%
“…The significant interaction of the Arabidopsis defense hormone perception with the B. cinerea isolates suggests that COI1 and NPR1 control the response of Arabidopsis when faced with a diversity of pathogen virulence mechanisms via one of two options (Weinig, 2000;Liefting et al, 2009;Palacio-López et al, 2015). First, COI1/NPR1 may canalize the plant's response by channeling the response to a diversity of stimuli/attacks into a single focused, coherent outcome.…”
Section: Genetic Variation In B Cinerea Identifies Different Canalizmentioning
confidence: 99%
“…Adaptive plasticity is common but not ubiquitous (Palacio-López, Beckage, Scheiner, & Molofsky, 2015), and biologists feel the lack of a predictive theory for when plasticity should evolve when they contemplate the limits to species' resilience to environmental change (e.g., Ashander, Chevin, & Baskett, 2016). Adaptive plasticity is common but not ubiquitous (Palacio-López, Beckage, Scheiner, & Molofsky, 2015), and biologists feel the lack of a predictive theory for when plasticity should evolve when they contemplate the limits to species' resilience to environmental change (e.g., Ashander, Chevin, & Baskett, 2016).…”
Section: Introductionmentioning
confidence: 99%